Developing oral health risk assessment as routine practice during early stages of clinical careers: A cross‐sectional study of dental students using the NoMAD questionnaire. (10th December 2019) - Cook, Clare; Finch, Tracy; Sharma, Samridh; Girling, Melissa; Rapley, Tim; Vernazza, Christopher R.
Abstract: Background: Effective implementation of healthcare initiatives is of key importance for ensuring high‐quality clinical and health outcomes. Using Normalization Process Theory, this study investigates the implementation behaviour of dental students in relation to a novel oral health risk assessment tool. It considers the impact of advancing learning on normalisation of innovative healthcare practice. Methods: Students completed the NoMAD (normalisation of complex interventions‐measure development) questionnaire and an additional scale to assess perceived value of the oral health risk assessment tool, after having used the tool for nearly one academic year. The sample comprised third‐ (n = 75), fourth‐ (n = 77) and fifth‐year (n = 37) students. Differences between groups in relation to the four generative processes of normalisation were analysed using ANOVA. Cohen's d effect sizes were calculated between groups. Multiple linear regression was undertaken to investigate the impact of normalisation level on value/utility judgements. Results: There were significant group differences for three of the four generative processes of normalisation (coherence, cognitive participation and reflexive monitoring). Third‐ and fourth‐year students were highly similar but these groups showed lower normalisation compared to fifth years. Normalisation assessment predicted perceived value and utility of the oral health risk assessment tool. Conclusions: The findings suggest that dental students show lower normalisation of novel tools at earlier stages in their course, possibly due to increased cognitive load, and that perceived value and utility of a novel tool is related to increased normalisation.